A census of early-phase high-mass star formation in the central molecular zone - Lu, Xing; Mills, Elisabeth A. C.; Ginsburg, Adam; Walker, Daniel L.; Barnes, Ashley T.; Butterfield, Natalie; Henshaw, Jonathan; Battersby, Cara; Kruijssen, Diederik; Longmore, Steven N.; Zhang, Qizhou; Bally, John; et al. (The astrophysical journal. Supplement series, 2019)
We present new observations of the C-band continuum emission and masers to assess high-mass (>8 ) star formation at early evolutionary phases in the inner 200 pc of the Central Molecular Zone (CMZ) of the Galaxy. The continuum observation is complete to free-free emission from stars above 10-11 in 91% of the covered area. We identify 104 compact sources in the continuum emission, among which five are confirmed ultracompact H ii regions, 12 are candidates of ultracompact H ii regions, and the remaining 87 sources are mostly massive stars in clusters, field stars, evolved stars, pulsars, extragalactic sources, or of unknown nature that is to be investigated. We detect class ii CH3OH masers at 23 positions, among which six are new detections. We confirm six known H2CO masers in two high-mass star-forming regions and detect two new H2CO masers toward the Sgr C cloud, making it the ninth region in the Galaxy that contains masers of this type. In spite of these detections, we find that current high-mass star formation in the inner CMZ is only taking place in seven isolated clouds. The results suggest that star formation at early evolutionary phases in the CMZ is about 10 times less efficient than expected from the dense gas star formation relation, which is in line with previous studies that focus on more evolved phases of star formation. This means that if there will be any impending, next burst of star formation in the CMZ, it has not yet begun.
Gesehen am 03.03.2020